Exploring the strengths of long term marriages among Malaysian Chinese couples / Teoh Gaik Kin - Teoh, Gaik Kin (2015)
With the emerging themes of Asian epistemologies and Asian forms of Psychology, the cultural discrepancy between the Western worlds and the Asians is marked. Western hegemony in the knowledge base of marriage has much to contribute, and yet Eastern perspectives are needed to bridge the gaps of human diversity. Thus, this study intended to understand the marital strengths of long term married couples among the Malaysian Chinese from an emic perspective. The research methodology utilized in this research was the qualitative approach. Five couples, with years of marriage ranging from 40 to 60 years, participated in this research through purposive sampling. In-depth interviews were carried out. The couples went through 3 to 4 interview sessions, with each lasting for 1½ to 2 hours. Multiple interviews were carried out to reach depth and richness in data, until the objective of the study is attained. The sessions were recorded with the consents of the participants. Two couples are Mandarin speaking and three couples are English speaking. They reside in urban areas. The sources of data were interviews, observation and field notes. Steps were taken to ensure the trustworthiness of the study. These steps include, member checking, tabling out the researcher’s biases, making clear the paradigmatic stance of the researcher, peer reviewing, employing multiple methods and multiple sources of data, being sensitive to relational oriented ethical practice and adequate engagement in data collection. The findings of this study revealed the strengths of long term marriages were tolerance, accommodativeness, empathy, love for the children, respectfulness for the elderly, social supports and religion. They were supported by reciprocal interaction between the couple and the children. The strengths were rooted in other-centered cultural value. The theme for the marital strengths was reciprocal based other-centeredness. The findings reflected both similarities and dissimilarities in the gravity of marriage between the West and Malaysian Chinese. The similarities between the West and East are intrinsic virtues, self-determinism, living iv beyond self-fulfillment and inner regulation which are required for betterment in marital relationship. The cultural values which gird the strengths diverge between the West and East. The findings also showed that marital strength comprised the interrelationship among individuals, social network and social influence. Marital strengths are community based. The theoretical implications and the practical implications - to marriage in postmodern generation, education system at home and school, marriage and family policies and counseling practice among the Chinese couples were discussed.